Capuchin monkeys do not show human-like pricing effects - Catapano, Rhia; Buttrick, Nicholas; Widness, Jane; Goldstein, Robin; Santos, Laurie R. (Frontiers in Psychology, 2014)
Recent work in judgment and decision-making has shown that a good’s price can have irrational effects on people’s preferences. People tend to prefer goods that cost more money and assume that such expensive goods will be more effective, even in cases where the price of the good is itself arbitrary. Although much work has documented the existence of these pricing effects, unfortunately little work has addressed where these price effects come from in the first place. Here we use a comparative approach to distinguish between different accounts of this bias and to explore the origins of these effects. Specifically, we test whether brown capuchin monkeys (Cebus apella) are also susceptible to pricing effects within the context of an experimentally trained token economy. Using a capuchin population previously trained in a token market, we explored whether monkeys used price as an indicator of value across four experiments. Although monkeys demonstrated an understanding of which goods had which prices (consistently shifting preferences to cheaper goods when prices were increased), we observed no evidence that such price information affected their valuation of different kinds of goods. These results suggest that human price effects may involve more sophisticated human-unique cognitive capacities, such as an understanding of market forces and signaling.